Chronic fondaparinux use in a hemodialysis patient with heparin‐induced thrombocytopenia type II and extracorporeal circuit thrombosis—A case report and review of the literature. Issue 3 (6th December 2012) - Brown, Paula; Jay, Richard; Fox, Andrea; Oliver, Matthew
Abstract: Heparin‐induced thrombocytopenia (HIT) is a potentially life‐threatening condition that can develop after exposure to unfractionated or low–molecular‐weight heparins. Treatment options appear to be limited in patients on concurrent intermittent hemodialysis. We report the case of an 88‐year‐old man newly initiated on high‐flux hemodialysis who developed HIT and extracorporeal circuit thrombosis after 3 weeks of exposure to unfractionated heparin. Our patient was successfully treated with fondaparinux 2.5 mg subcutaneously three times per week and citrate during dialysis sessions. Antifactor Xa levels were measured on several occasions while receiving fondaparinux.